Prauserella flavalba sp. nov., a novel species of the genus Prauserella, isolated from alkaline soil. Issue 1 (3rd February 2020) - Li, Qinyuan; Rückert, Christian; Li, Guiding; Huang, Ping; Schneider, Olha; Kalinowski, Jörn; Jiang, Yi; Zotchev, Sergey B.; Jiang, Chenglin
Abstract : A Gram-strain positive, mycelium-forming actinomycete, YIM 121212 T, was isolated from an alkaline soil sample collected in Yunnan province, PR China. Classification using a polyphasic approach indicated that YIM 121212 T represents a member of the genus Prauserella, and is closely related to Prauserella coralliicola SCSIO 11529 T (99.31 %), Prauserella endophytica SP28S-3 T (99.17 %), Prauserella soli 12-833 T (97.43 %), Prauserella oleivorans RIPI T (97.03 %), Prauserella marina MS498 T (96.74 %), Prauserella rugosa DSM 43194 T (96.54 %) and Prauserella muralis 05-Be-005 T (95.92 %). Average nucleotide identity values (ANI) of YIM 121212 T to P. coralliicola DSM 45821 T and P. endophytica CGMCC 4.7182 T were 93.1 and 92.8 %, respectively, which were lower than the threshold of 95 %. The digital DNA–DNA hybridization (dDDH) values between YIM 121212 T and these two species were 50.8 and 49.9 %, respectively and thus were also well below the cut off value (>70 %) for species delineation. The DNA G+C content of YIM 121212 T is 70.8 mol%. Major fatty acids are iso -C16 : 0, iso -C16 : 1 H, C16 : 1 ω7 c / iso -C15 : 0 2OH, C17 : 1 ω6 c, and C17 : 1 ω8 c . The predominant menaquinone is MK-9(H4 ). The polar lipid profile consists of diphosphatidylglycerol (DPG), phosphatidylglycerol (PG), phosphatidylethanolamine (PE), phosphatidylmethylethanolamine (PME), phosphatidylinositol (PI), and phosphatidylinositol mannoside (PIM). The draft genomes were further analyzed for the presence of secondary metabolite biosynthesis (SMB) gene clusters. On the basis of the above observations, YIM121212 T can be distinguished from closely related species belonging to the genus Prauserella . Thus, YIM121212 T represents a novel species of the genus Prauserella, for which the name Prauserella flavalba sp. nov. is proposed. The type strain is YIM121212 T (=CCTCC AA 2013011 T =DSM 45973 T ).